2016
DOI: 10.1161/circulationaha.116.023402
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Comparison of Prasugrel Versus Ticagrelor in Patients With Type 2 Diabetes Mellitus and Coronary Artery Disease

Abstract: BACKGROUND:Patients with diabetes mellitus (DM) are at increased risk of atherothrombotic events, underscoring the importance of effective platelet inhibiting therapies. Prasugrel and ticagrelor reduce thrombotic complications to a greater extent than clopidogrel. Subgroup analyses of pivotal clinical trials testing prasugrel and ticagrelor versus clopidogrel showed DM patients to have benefits that were consistent with the overall trial populations, although the magnitude of the ischemic risk reduction appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(17 citation statements)
references
References 35 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…For instance, our study generates the hypothesis that periprocedural GV and HbA1c assessment may help to identify those diabetic patients that should be moved towards more aggressive antiplatelet management, such as ticagrelor, also in the setting of an elective procedure [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, our study generates the hypothesis that periprocedural GV and HbA1c assessment may help to identify those diabetic patients that should be moved towards more aggressive antiplatelet management, such as ticagrelor, also in the setting of an elective procedure [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with DM had a greater reduction in ischemic events without an increase in major bleeding and therefore had a greater net treatment benefit with prasugrel compared to patients without DM [ 12 ]. Ticagrelor exerts similar or greater inhibition of platelet reactivity compared to prasugrel in DM patients with coronary artery disease [ 15 ]. Therefore, we hypothesized that we would observe a less negative impact of DM on the prognosis of patients in PRAGUE-18 compared to older studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although the semaglutide trial showed significant beneficial effects on nonfatal stroke, the cardiovascular outcome trials were underpowered for the specific stroke endpoints. More studies using ertugliflozin (SGLT2 inhibitor) and dulaglutide (once-weekly GLP1 analogue) are currently ongoing in the hope of improving vascular outcomes and total mortality in patients with diabetes at high stroke risk [83,84]. Until the results of these studies are released, multifactorial interventions targeting individual cerebrovascular risk factors are required to improve clinical outcomes in diabetes patients after a stroke or at high risk of stroke.…”
Section: Discussionmentioning
confidence: 99%